Challenges in pancreas transplantation - Sharples, E; Mittal, S; Friend, P (Springer Verlag, 2016)
Whole-organ pancreas transplantation, either alone or combined with a kidney transplant, is the only definitive treatment for many patients with type 1 diabetes that restores normal glucose homoeostasis and insulin independence. Pancreas transplantation delays, or potentially prevents, secondary diabetes complications and is associated with improvement in patient survival when compared with either patients remaining on the waiting list or those receiving kidney transplant alone. Pancreas transplantation is safe and effective, with 1-year patient survival >97 % and graft survival rates of 85 % at 1 year and 76 % at 5 years in recent UK data. This review focuses on some current areas of interest in pancreas transplantation.